Sulfur-doped iron Fe-S-N-C cathode oxygen reduction catalyst as well as preparation method and application thereof

By doping sulfur atoms and uniformly dispersing iron and sulfur on a nitrogen-coated nitrogen carbon substrate, Fe-S-N-C cathode oxygen reduction catalyst was prepared, which solved the problem of poor membrane electrode performance of single atomic catalysts in fuel cells, and achieved high catalytic activity and stability of oxygen reduction catalytic effect.

CN119581581AActive Publication Date: 2025-03-07UNIV OF SCI & TECH OF CHINA
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411852181.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-07
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

In proton exchange membrane fuel cells, there is still a large gap in the membrane electrode performance between non-precious metal single-atom catalysts and platinum-based catalysts, and it is difficult to achieve oxygen reduction catalytic activity and stability comparable to platinum-based catalysts.

Method used

By doping sulfur atoms, the symmetric structure of Fe-N4 active sites is broken, the spin and charge density of Fe-N4 active center is changed, and iron and sulfur are uniformly dispersed on a nitrogen-coated nitrogen carbon substrate through chemical vapor deposition to prepare a sulfur-doped iron Fe-S-N-C cathode oxygen reduction catalyst.

Benefits of technology

The catalytic activity and stability of the Fe-S-N-C cathode oxygen reduction catalyst is improved, the adsorption energy of the active site and the oxygen intermediate is improved, the rate of oxygen reduction reaction is enhanced, and the dissolution of iron is inhibited.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581581A_ABST
    Figure CN119581581A_ABST
Patent Text Reader

Abstract

The invention provides a sulfur-doped iron Fe-S-N-C cathode oxygen reduction catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalysts and preparation thereof. The preparation method comprises the steps that ZIF-8 of a regular dodecahedron frame structure and a nitrogen-containing ligand are mixed and pyrolyzed, a nitrogen-coated nitrogen-carbon substrate is formed, and the nitrogen-carbon substrate is of a regular dodecahedron frame structure; and performing chemical vapor deposition on the precursor iron salt, the precursor sulfur salt and the nitrogen-coated nitrogen-carbon substrate to obtain the sulfur-doped iron Fe-S-N-C cathode oxygen reduction catalyst. According to the invention, electrons around the Fe active center are reduced, the interaction with oxygenates is improved, the oxygen reduction process of four-electron transfer is promoted during subsequent application, meanwhile, the dissolution of Fe is reduced, and the cycling stability of the catalyst is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts and preparation thereof, and in particular to a sulfur-doped iron Fe-SNC cathode oxygen reduction catalyst and a preparation method and application thereof. Background Art

[0002] Proton exchange membrane fuel cell (PEMFC) is a new type of energy conversion device. It has received widespread attention due to its environmental friendliness, low cost, and high theoretical energy density. The oxygen reduction reaction (ORR) is a key electrochemical reaction in fuel cell applications. Since the reaction involves four electron transfers and has slow reaction kinetics, the development of high-performance and relatively stable ORR electrocatalysts is the focus of the development of proton exchange membrane fuel cells.

[0003] Traditional platinum-based catalysts are scarce and expensive, which hinders the widespread application of proton exchange membrane fuel cells. Therefore, the development of non-precious metal alternative catalysts is considered to be the key to achieving large-scale application of proton exchange membrane fuel cells.

[0004] Single-atom catalysts have advantages such as high atomic utilization efficiency, adjustable coordination structure and designable geometric configuration, and single-atom catalysts have ORR catalytic activity comparable to that of platinum-based catalysts in acidic media. However, in proton exchange membrane fuel cells, there is still a large gap in membrane electrode performance between single-atom catalysts and platinum-based catalysts. Summary of the invention

[0005] In view of this, in order to at least partially solve at least one of the above-mentioned technical problems, the present invention provides a sulfur-doped iron Fe-SNC cathode oxygen reduction catalyst and a preparation method and application thereof.

[0006] According to an embodiment of one aspect of the present invention, a method for preparing a sulfur-doped iron Fe-SNC cathode oxygen reduction catalyst is provided, comprising: pyrolyzing a mixture of ZIF-8 having a regular dodecahedral framework structure and a nitrogen-containing ligand to form a nitrogen-coated nitrogen-carbon substrate, wherein the nitrogen-carbon substrate has a regular dodecahedral framework structure; and chemically vapor depositing a precursor iron salt, a precursor sulfur salt, and the nitrogen-coated nitrogen-carbon substrate to obtain a sulfur-doped iron Fe-SNC cathode oxygen reduction catalyst.

[0007] According to an embodiment of the present invention, the temperature of chemical vapor deposition is 750-900° C., and the time is 2-4 hours; wherein the atmosphere of chemical vapor deposition is a mixture of argon and hydrogen, or argon.

[0008] According to an embodiment of the present invention, ZIF-8 having a regular dodecahedral framework structure is mixed with nitrogen-containing ligands and pyrolyzed to form a nitrogen-coated nitrogen-carbon substrate, including: dissolving ZIF-8 and nitrogen-containing ligands in a solvent and mixing them to obtain a suspension; subjecting the suspension to rotary evaporation, drying, and grinding in sequence to obtain nitrogen-coated ZIF-8; under a protective atmosphere, pyrolyzing the nitrogen-coated ZIF-8 to obtain a nitrogen-coated nitrogen-carbon substrate; wherein the nitrogen-containing ligands include at least one of o-phenanthroline and dopamine.

[0009] According to an embodiment of the present invention, the pyrolysis temperature is 900-1000° C., the time is 0.5-1.5 h; and the solvent includes a mixed solution of water and ethanol.

[0010] According to an embodiment of the present invention, when the nitrogen-containing ligand is o-phenanthroline, the mass ratio of ZIF-8 to the nitrogen-containing ligand is (3-5):1.

[0011] According to an embodiment of the present invention, the precursor iron salt includes at least one of ferrocene, ferrous chloride, and ferrous chloride hydrate; the precursor sulfur salt includes at least one of thiourea and sublimated sulfur; the molar ratio of the precursor iron salt, the precursor sulfur salt, and the nitrogen-coated nitrogen-carbon substrate is 1:1:(1.6~3.2).

[0012] According to an embodiment of the present invention, ZIF-8 is prepared by the following process: zinc nitrate and dimethylimidazole are dissolved in a methanol solution and mixed to obtain a mixed solution; the mixed solution is centrifuged and dried in sequence to obtain ZIF-8.

[0013] According to an embodiment of the present invention, the mass ratio of zinc nitrate to dimethylimidazole is (4-8):(11-15).

[0014] According to another embodiment of the present invention, there is provided a sulfur-doped iron Fe-SNC cathode oxygen reduction catalyst prepared by the above-mentioned preparation method, comprising: a nitrogen-coated nitrogen-carbon substrate having a regular dodecahedral framework structure, wherein sulfur is loaded on the nitrogen-coated nitrogen-carbon substrate, sulfur interacts with the nitrogen-coated nitrogen-carbon substrate, sulfur doping changes the bond energy of the iron-nitrogen bond, and inhibits the dissolution of iron; and an active center, comprising Fe-N loaded inside the nitrogen-coated nitrogen-carbon substrate. 4 .

[0015] According to another embodiment of the present invention, there is provided an application of the above-mentioned Fe-SNC cathode oxygen reduction catalyst in the technical field of cathode of proton exchange membrane fuel cells.

[0016] According to an embodiment of the present invention, a nitrogen-coated nitrogen-carbon substrate is formed by mixing a nitrogen-containing ligand with ZIF-8 for pyrolysis. The introduction of nitrogen provides an electron donor, which helps to anchor more iron in the subsequent reaction and enhance the electron density around the iron active center. In the oxygen reduction reaction, the introduction of nitrogen helps to promote the adsorption and activation of oxygen molecules by changing the local electronic structure, thereby accelerating the reaction rate. Furthermore, iron and sulfur are introduced into the nitrogen-coated nitrogen-carbon substrate by chemical vapor deposition, and the Fe-N bond is broken by sulfur doping. 4 The symmetry of the site changes the Fe-N 4 The spin and charge density of the active center. In the application of oxygen reduction reaction, it helps to improve the Fe-N 4 The adsorption energy of active sites and oxygen intermediates improves the catalytic activity of Fe-SNC cathode oxygen reduction catalyst. In addition, the addition of sulfur causes the nitrogen-carbon substrate to form a structure similar to thiophene (C@S@C), which helps to change the bond energy of the iron-nitrogen bond, inhibits the process of iron dissolution into particles, and improves the stability of Fe-SNC cathode oxygen reduction catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A flow chart showing a method for preparing a Fe-SNC cathode oxygen reduction catalyst according to an embodiment of the present invention is shown;

[0018] Figure 2 The scanning electron microscope image of ZIF-8 prepared in Example 1 of the present invention is shown;

[0019] Figure 3 The scanning electron microscope image of the nitrogen-coated nitrogen-carbon substrate prepared in Example 1 of the present invention is shown;

[0020] Figure 4 The cyclic voltammetry test curves of the Fe-SNC cathode oxygen reduction catalyst 1, the platinum-based catalyst, and the FeNC oxygen reduction catalyst 1' prepared in Comparative Example 1 in 0.1M perchloric acid solution are shown;

[0021] Figure 5 The half-wave potential curves of the Fe-SNC cathode oxygen reduction catalyst 1 prepared in Example 1 of the present invention before and after accelerated aging tests of 0, 10,000, 30,000 and 50,000 cycles at 0.6-0.9V in a 0.1M perchloric acid solution are shown;

[0022] Figure 6 The diagram shows the hydrogen-oxygen polarization curves of the Fe-SNC cathode oxygen reduction catalyst 1 prepared in Example 1 of the present invention and the FeNC oxygen reduction catalyst 1' prepared in Comparative Example 1 respectively applied in the cathode of a proton exchange membrane fuel cell measured in an 850e fuel cell test system; and

[0023] Figure 7 The half-wave potential curve of the Fe-SNC cathode oxygen reduction catalyst 6 prepared by calcining in an argon atmosphere in Example 6 of the present invention is shown. DETAILED DESCRIPTION

[0024] Below, embodiments of the present invention will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of embodiments of the present invention. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of concepts of the present invention.

[0025] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. The term "comprising" used herein indicates the existence of features, steps, operations, but does not exclude the existence or addition of one or more other features.

[0026] In the case of using expressions such as "at least one of A, B, and C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, and C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.). In the case of using expressions such as "at least one of A, B, or C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, or C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.).

[0027] Traditionally, platinum-based catalysts are mostly used as cathode catalysts in proton exchange membrane fuel cells. However, platinum-based catalysts require the use of relatively expensive precious metals, and their application process costs are relatively high. In related technologies, non-precious metal catalysts are usually used to selectively replace platinum-based catalysts. However, the catalytic activity and stability of non-precious metal catalysts are inferior to those of platinum-based catalysts.

[0028] In the process of realizing the concept of the present invention, it was found that the preparation of Fe-N 4Fe-NC single-atom catalysts can easily achieve oxygen reduction catalytic activity comparable to that of Pt-based catalysts in acidic media. However, there is still a large gap in membrane electrode performance between Fe-NC catalysts and Pt-based catalysts in proton exchange membrane fuel cells.

[0029] Furthermore, in order to solve the above problems, sulfur atoms with different atomic radii and electronegativity are doped to break the Fe-N 4 The symmetric structure of the active site changes the Fe-N 4 The spin and charge density of the active center can be improved, thereby improving the adsorption energy between the active site and the oxygen intermediate, which can improve the catalytic activity of the Fe-SNC cathode oxygen reduction catalyst. In addition, the addition of sulfur makes the carrier ZIF-8 form a thiophene-like structure (C@S@C), reducing the Fe-N 4 The electrons around the active center improve the Fe-N 4 The interaction between the active centers and oxygenates promotes the complete four-electron transfer oxygen reduction process in acidic solution, reduces the dissolution of iron, and improves the stability of the Fe-SNC cathode oxygen reduction catalyst.

[0030] Specifically, according to an embodiment of one aspect of the present invention, a method for preparing a sulfur-doped iron Fe-SNC cathode oxygen reduction catalyst is provided. Figure 1 A flow chart of a method for preparing a Fe-SNC cathode oxygen reduction catalyst according to an embodiment of the present invention is shown. Figure 1 As shown, the preparation method includes operations S101~S102.

[0031] In operation S101 , ZIF-8 having a regular dodecahedral framework structure is mixed with a nitrogen-containing ligand and pyrolyzed to form a nitrogen-coated nitrogen-carbon substrate, wherein the nitrogen-carbon substrate has a regular dodecahedral framework structure.

[0032] According to an embodiment of the present invention, ZIF-8 having a regular dodecahedral framework structure is used as a carrier, which can maintain a high specific surface area and a relatively rich pore structure after pyrolysis, which helps to increase the number of active sites for subsequent catalyst formation, thereby improving the catalytic effect. The nitrogen-coated nitrogen-carbon substrate not only increases the nitrogen content of the nitrogen-carbon substrate, but also forms a uniform distribution of nitrogen on the surface of the nitrogen-carbon substrate, thereby providing more active sites. The nitrogen-coated structure may contain a variety of nitrogen species, such as pyridinic nitrogen, pyrrolic nitrogen or graphitic nitrogen, etc. These different nitrogen species can form Fe-N bonds with the iron active center. 4 The coordination structure improves the catalytic activity and stability of Fe-SNC cathode oxygen reduction catalyst.

[0033] In operation S102, a precursor iron salt, a precursor sulfur salt and a nitrogen-coated nitrogen-carbon substrate are chemically vapor deposited to obtain a sulfur-doped iron Fe-SNC cathode oxygen reduction catalyst.

[0034] According to an embodiment of the present invention, iron and sulfur are uniformly dispersed on a nitrogen-coated nitrogen-carbon substrate by chemical vapor deposition, ensuring uniform distribution of active sites of iron and sulfur, and improving single-atom utilization and catalytic activity of Fe. The introduction of nitrogen improves the conductivity of the carbon-based material, and the introduction of sulfur further optimizes the electron transmission path. Sulfur atoms act as a bridge for electron transmission, enhancing the electron conductivity inside the catalyst material.

[0035] For example, the process of chemical vapor deposition can be understood as: placing the precursor iron salt and the precursor sulfur salt in the lower part of the container, placing the nitrogen-coated nitrogen-carbon substrate in the upper part of the container, and separating the upper and lower parts of the container with a gas phase membrane, the container used can be, for example, a porcelain boat. Then, pyrolysis is performed to make the precursor iron salt and the precursor sulfur salt form gaseous forms respectively, and then deposited on the nitrogen-coated nitrogen-carbon substrate after passing through the gas phase membrane.

[0036] According to an embodiment of the present invention, when chemical vapor deposition is used, due to the different atomic diffusion rates of iron and sulfur, voids or pores may appear at the diffusion interface, that is, when sulfur doping is used, the Kirkendall effect (forming voids or pores) occurs, and the nitrogen-coated nitrogen-carbon substrate is etched, so that the nitrogen-carbon substrate has more abundant micropores and mesopores, thereby increasing the active site density of the Fe-SNC cathode oxygen reduction catalyst, and when used in the oxygen reduction process, it is convenient for oxygen to reach the Fe-N 4 The introduction of sulfur atoms changes the electronic structure of iron and improves the catalytic activity of iron, making each Fe-N 4 The intrinsic activity of the active site is improved. In addition, the preparation method of the present invention is simple, easy to operate, and suitable for large-scale production and promotion.

[0037] According to an embodiment of the present invention, the temperature of chemical vapor deposition is 750-900°C, for example, it can be 750°C, 800°C, 850°C or 900°C, preferably 900°C. The time is 2-4h, for example, it can be 2h, 3h or 4h, preferably 3h. Setting the temperature and time of chemical vapor deposition in the above range helps to promote the precursor iron salt and the precursor sulfur salt to be fully converted into a gaseous state, so that iron and sulfur can be evenly loaded on the nitrogen-coated nitrogen-carbon substrate. Among them, the atmosphere of chemical vapor deposition is a mixture of argon and hydrogen, or argon. Preferably, the atmosphere of chemical vapor deposition is a mixture of 10% by volume of hydrogen and argon. Adding the above mass percentage of hydrogen into argon helps to provide a reducing atmosphere, which can reduce the iron salt to metallic iron, so that the iron atoms are in the form of Fe-N4 Active sites exist in the Fe-SNC cathode oxygen reduction catalyst. At the same time, 10% hydrogen can etch the nitrogen-coated nitrogen-carbon substrate, thereby further increasing the specific surface area of ​​the nitrogen-carbon substrate and helping to improve the catalytic activity of the Fe-SNC cathode oxygen reduction catalyst.

[0038] According to an embodiment of the present invention, operation S101 includes sub-operations S1011 to S1013.

[0039] In sub-operation S1011, ZIF-8 and the nitrogen ligands contained therein are dissolved in a solvent and mixed to obtain a suspension.

[0040] In sub-operation S1012, the suspension is subjected to rotary evaporation, drying, and grinding in sequence to obtain nitrogen-coated ZIF-8.

[0041] In sub-operation S1013, the nitrogen-coated ZIF-8 is pyrolyzed under a protective atmosphere to obtain a nitrogen-coated nitrogen-carbon substrate.

[0042] According to an embodiment of the present invention, the nitrogen-containing ligand includes at least one of o-phenanthroline and dopamine, preferably o-phenanthroline. The nitrogen coating method helps to improve the chemical stability and thermal stability of ZIF-8, and helps to better maintain the integrity of the structure at a higher temperature (1000°C). By mixing the nitrogen-containing ligand with ZIF-8 and rotary evaporation, a relatively large amount of nitrogen atoms can be introduced into the ZIF-8 structure. The introduced nitrogen atoms will be fixed on ZIF-8 during the subsequent pyrolysis process, thereby increasing the nitrogen doping level, providing more N active sites, and subsequently being able to bond with more Fe to enhance the catalytic efficiency.

[0043] Specifically, in sub-operation S1011, the mixing time is 12 hours. The solvent includes a mixed solution of water and ethanol, and more specifically, in the mixed solution, the volume ratio of ethanol to water is 2:1. Mixing water with ethanol helps to lower the boiling point of the mixed solution, and lowers the boiling point to about 70°C. In the subsequent rotary evaporation process, the removal of the solvent is simpler and more convenient. In sub-operation S1013, the pyrolysis temperature is 900~1000°C, for example, it can be 900°C, 950°C or 1000°C, preferably 1000°C, the pyrolysis time is 0.5~1.5h, for example, it can be 0.5h, 1h or 1.5h, preferably 1h, the pyrolysis method can be, for example, roasting by a tubular furnace, and the pyrolysis atmosphere can be, for example, argon.

[0044] In sub-operation S1012, the temperature of the rotary evaporation is 70-80°C, for example, 70°C, 75°C or 80°C, preferably 70°C, and the speed of the rotary evaporation is, for example, 121 rpm. Adjusting the temperature and speed within the above range is helpful to remove the solvent by rotary evaporation.

[0045] According to an embodiment of the present invention, when the nitrogen-containing ligand is o-phenanthroline, the mass ratio of ZIF-8 to the nitrogen-containing ligand is (3-5): 1, preferably 4: 1. O-phenanthroline contains two nitrogen atoms. Compared with other nitrogen-containing ligands, it can introduce more nitrogen atoms under the same mass ratio conditions to improve the nitrogen doping level. In the process of relevant experiments, when the mass ratio of the two is lower than the above range, the conductivity of the obtained nitrogen-carbon substrate is poor; when the mass ratio of the two is higher than the above range, the nitrogen doping amount in the obtained nitrogen-carbon substrate is less, which is not conducive to the subsequent bonding with Fe.

[0046] According to an embodiment of the present invention, the precursor iron salt includes at least one of ferrocene, ferrous chloride, and ferrous chloride hydrate; the precursor sulfur salt includes at least one of thiourea and sublimated sulfur. The boiling points of the above-mentioned precursor iron salt and the precursor sulfur salt are between 100 and 200°C, and can be mixed relatively evenly during the vapor deposition process, thereby forming a uniform distribution of iron and sulfur. The molar ratio of the precursor iron salt, the precursor sulfur salt, and the nitrogen-coated nitrogen-carbon substrate is 1:1:(1.6~3.2), for example, it can be 1:1:1.6, 1:1:2, 1:1:2.5, 1:1:3 or 1:1:3.2. In the process of screening the molar ratio of the three, it was found that when the molar ratio of the three was adjusted to the above range, it was helpful to fully load iron and sulfur on the nitrogen-carbon substrate.

[0047] According to an embodiment of the present invention, ZIF-8 is prepared by the following process: zinc nitrate and dimethylimidazole are dissolved in a methanol solution and mixed to obtain a mixed solution; the mixed solution is centrifuged and dried in sequence to obtain ZIF-8.

[0048] In one embodiment, zinc nitrate is dissolved in a methanol solution to obtain a zinc nitrate solution. Dimethylimidazole is dissolved in a methanol solution to obtain a dimethylimidazole solution. The zinc nitrate solution is added to the dimethylimidazole solution, stirred and mixed to obtain a mixed solution. Zinc nitrate and dimethylimidazole have high solubility in methanol, and zinc ions and dimethylimidazole molecules are formed during the dissolution process. During the mixing process, the two interact through electrostatic attraction to form a complex. As needed, the mixture can be left to stand for a period of time to promote the complex to assemble into the crystal structure of ZIF-8. Unreacted raw materials and by-products are then removed by centrifugation, and residual solvent is removed by drying.

[0049] According to an embodiment of the present invention, the mass ratio of zinc nitrate to dimethylimidazole is (4-8): (11-15), preferably 6: 13. For example, 6 g of zinc nitrate can be dissolved in 80 mL of methanol solution to form a zinc nitrate solution, and 13 g of dimethylimidazole can be dissolved in 160 mL of methanol solution to form a dimethylimidazole solution.

[0050] Preferably, the mixing time for the mixed solution is (22-26) hours, preferably 24 hours, the speed of centrifugal separation is 10000 rpm, and the centrifugal time is (3-5) minutes, preferably 5 minutes. The drying method can be, for example, vacuum drying, the drying temperature is 55-60°C, and the drying time is 6 hours.

[0051] In a specific embodiment, the preparation process of the Fe-SNC cathode oxygen reduction catalyst is as follows:

[0052] Dissolve zinc nitrate in methanol solution to obtain a zinc nitrate solution.

[0053] Dissolve dimethylimidazole in methanol solution to obtain a dimethylimidazole solution.

[0054] The zinc nitrate solution is added to the dimethylimidazole solution, and the mixture is stirred to obtain a mixed solution.

[0055] The mixed solution was centrifuged, washed with methanol and vacuum dried in sequence to obtain ZIF-8.

[0056] ZIF-8 and nitrogen-containing ligands were dissolved in a mixed solution of ethanol and water, and then subjected to rotary evaporation, grinding, and pyrolysis in sequence to obtain a nitrogen-coated nitrogen-carbon substrate.

[0057] In an atmosphere of 10% by volume hydrogen mixed with argon, precursor iron salt, precursor sulfur salt and nitrogen-coated nitrogen-carbon substrate were chemically vapor deposited to obtain sulfur-doped iron Fe-SNC cathode oxygen reduction catalyst.

[0058] According to another embodiment of the present invention, there is provided a sulfur-doped iron Fe-SNC cathode oxygen reduction catalyst prepared by the above-mentioned preparation method, comprising: a nitrogen-coated nitrogen-carbon substrate having a regular dodecahedral framework structure, wherein sulfur is uniformly dispersed on the nitrogen-coated nitrogen-carbon substrate and interacts with the nitrogen-coated nitrogen-carbon substrate, and sulfur doping changes the bond energy of the iron-nitrogen bond and inhibits the dissolution of iron; and an active center, comprising Fe-N supported inside the nitrogen-coated nitrogen-carbon substrate. 4 .

[0059] According to an embodiment of the present invention, the single-atom center of iron is tightly combined with the nitrogen-carbon substrate through the Fe-N bond to form an active center Fe-N 4 , has high catalytic activity and high stability in oxygen reduction reaction. By doping with sulfur, the oxygen conductivity of Fe-SNC cathode oxygen reduction catalyst and the catalytic activity of Fe single atoms on active sites are improved, and the dissolution of iron in the form of particles is suppressed, which improves the stability of Fe single atoms.

[0060] According to an embodiment of the present invention, the mass fraction of Fe single atoms is 3-6%, for example, 3%, 4%, 5% or 6%. This indicates that coating nitrogen on the nitrogen-carbon substrate helps to fix more Fe, thereby optimizing the Fe-N 4 The electronic structure of the active center improves the catalytic efficiency.

[0061] According to another embodiment of the present invention, there is provided an application of the Fe-SNC cathode oxygen reduction catalyst as described above in the field of cathode technology of proton exchange membrane fuel cells.

[0062] According to an embodiment of the present invention, the Fe-N 4 The active center has high intrinsic activity and can efficiently catalyze the oxygen reduction reaction. Nitrogen doping and Liu doping on the carbon substrate further optimize the Fe-N 4 The electronic structure of the active center improves the catalytic efficiency, making the Fe-SNC cathode oxygen reduction catalyst have a higher half-wave potential, and can effectively catalyze the oxygen reduction reaction at a lower potential, thereby improving the voltage output and energy efficiency of the fuel cell. It also has high catalytic activity and stability, significantly improving the performance of the fuel cell and extending the service life of the battery.

[0063] In one of the embodiments, the half-wave potential of the Fe-SNC cathode oxygen reduction catalyst can reach 0.86V, which has a wide range of applicability in the field of proton exchange membrane fuel cell technology.

[0064] The present invention is further described below by embodiments and related test experiments and results thereof. In the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present invention. However, it is obvious that one or more embodiments may also be implemented without these specific details. And, in the absence of conflict, the details in the following embodiments may be combined into other feasible embodiments at will.

[0065] It should be noted that the following specific examples are only for illustration, and the protection scope of the present invention is not limited thereto. The chemicals and raw materials used in the following examples are all commercially available or homemade by recognized processing methods.

[0066] Embodiment 1:

[0067] 6 g of zinc nitrate was dissolved in 80 mL of methanol solution to obtain a zinc nitrate solution. 13 g of dimethylimidazole was dissolved in 160 mL of methanol solution to obtain a dimethylimidazole solution. Under stirring conditions, the zinc nitrate solution was added to the dimethylimidazole solution, and the first suspension was obtained after stirring for 24 hours. The first suspension was centrifuged at a centrifugal speed of 10,000 rpm for 5 minutes, washed three times with methanol, and then dried in a vacuum oven at 60°C to obtain ZIF-8.

[0068] Figure 2 FIG. 2 shows a scanning electron microscope image of ZIF-8 prepared in Example 1 of the present invention. Figure 2 As shown, it can be seen that the ZIF-8 prepared in Example 1 has a regular dodecahedral structure.

[0069] ZIF-8 and o-phenanthroline are dissolved in a mixed solution in a mass ratio of 4:1, wherein the mixed solution is prepared by mixing ethanol and water in a volume ratio of 2:1, and stirred for 12 hours to obtain a second suspension; the second suspension is subjected to rotary evaporation, vacuum drying and grinding to obtain a composite solid; the composite solid is pyrolyzed under argon conditions at 1000°C for one hour to obtain a nitrogen-coated nitrogen-carbon substrate.

[0070] Figure 3 FIG. 2 shows a scanning electron microscope image of a nitrogen-coated nitrogen-carbon substrate prepared in Example 1 of the present invention. Figure 3 As shown, it can be seen that the nitrogen-carbon substrate is coated with a nitrogen layer without much change in the basic structure.

[0071] Chemical vapor deposition process: ferrocene and thiourea are placed in the lower part of the porcelain boat, and the nitrogen-coated nitrogen-carbon substrate is placed in the upper part of the porcelain boat. The molar ratio of the three is 1:1:1.6. They are pyrolyzed at 750°C in an atmosphere of 10% hydrogen mixed with argon for 3 hours to obtain the sulfur-doped FeSNC single-atom oxygen reduction catalyst 1.

[0072] Comparative Example 1:

[0073] The preparation process of this comparative example 1 is substantially the same as that of example 1, except that only ferrocene is loaded into the lower part of the porcelain boat, and the addition ratio of ferrocene to the nitrogen-coated nitrogen-carbon substrate is 1:2, thereby obtaining a FeNC oxygen reduction catalyst 1'.

[0074] Figure 4 The cyclic voltammetry test curves of the Fe-SNC cathode oxygen reduction catalyst 1 prepared in Example 1 of the present invention, the commercially available platinum-based catalyst, and the Fe-NC oxygen reduction catalyst 1' prepared in Comparative Example 1 in 0.1M perchloric acid solution are shown. Figure 4As shown, it can be seen that the Fe-SNC cathode oxygen reduction catalyst 1 prepared in Example 1 exhibits excellent acidic oxygen reduction activity, and its half-wave potential can reach 0.86V, which is far superior to the Fe-NC oxygen reduction catalyst 1', and has better oxygen reduction activity than commercially available platinum-based catalysts.

[0075] Figure 5 The graph shows the half-wave potential curve of the Fe-SNC cathode oxygen reduction catalyst 1 prepared in Example 1 of the present invention before and after accelerated aging tests of 0, 10,000, 30,000 and 50,000 cycles at 0.6-0.9V in a 0.1M perchloric acid solution. Figure 5 As shown, the Fe-SNC cathode oxygen reduction catalyst 1 exhibits relatively excellent acidic oxygen reduction stability.

[0076] Figure 6 The figure shows the hydrogen-oxygen polarization curves of the Fe-SNC cathode oxygen reduction catalyst 1 prepared in Example 1 of the present invention and the FeNC oxygen reduction catalyst 1' prepared in Comparative Example 1 respectively applied in the cathode of a proton exchange membrane fuel cell measured in an 850e fuel cell test system. Figure 6 As shown, Fe-SNC cathode oxygen reduction catalyst 1 exhibits better cell performance than FeNC oxygen reduction catalyst 1'. ICP results show that the iron content in the FeSNC catalyst is 5.6wt%, and the iron content in the FeNC catalyst is 4.6wt%.

[0077] Embodiment 2:

[0078] The preparation process of this embodiment 2 is substantially the same as that of embodiment 1, except that the pyrolysis temperature during the chemical vapor deposition process is adjusted to 800° C., and the Fe-SNC cathode oxygen reduction catalyst 2 is prepared.

[0079] The Fe-SNC cathode oxygen reduction catalyst 2 prepared in Example 2 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe-SNC cathode oxygen reduction catalyst 2 was found to be 0.853V.

[0080] Embodiment 3:

[0081] The preparation process of this embodiment 3 is substantially the same as that of embodiment 1, except that the pyrolysis temperature during the chemical vapor deposition process is adjusted to 900° C., and a Fe-SNC cathode oxygen reduction catalyst 3 is prepared.

[0082] The Fe-SNC cathode oxygen reduction catalyst 3 prepared in Example 3 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe-SNC cathode oxygen reduction catalyst 3 was found to be 0.856V.

[0083] Embodiment 4:

[0084] The preparation process of this Example 4 is substantially the same as that of Example 3, except that during the preparation of ZIF-8, the stirring time of the dimethylimidazole solution and the zinc nitrate solution is adjusted to 22 h, and the Fe-SNC cathode oxygen reduction catalyst 4 is prepared.

[0085] The Fe-SNC cathode oxygen reduction catalyst 4 prepared in Example 4 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe-SNC cathode oxygen reduction catalyst 4 was found to be 0.849V.

[0086] Embodiment 5:

[0087] The preparation process of this Example 5 is substantially the same as that of Example 3, except that during the preparation of ZIF-8, the stirring time of the dimethylimidazole solution and the zinc nitrate solution is adjusted to 26 h, and the Fe-SNC cathode oxygen reduction catalyst 5 is prepared.

[0088] The Fe-SNC cathode oxygen reduction catalyst 5 prepared in Example 5 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe-SNC cathode oxygen reduction catalyst 5 was found to be 0.851V.

[0089] Embodiment 6:

[0090] The preparation process of this embodiment 6 is substantially the same as that of embodiment 3, except that the atmosphere during the chemical vapor deposition process is adjusted to an argon atmosphere to prepare a Fe-SNC cathode oxygen reduction catalyst 6.

[0091] The Fe-SNC cathode oxygen reduction catalyst 6 prepared in Example 6 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe-SNC cathode oxygen reduction catalyst 6 was found to be 0.842V.

[0092] Figure 7 The half-wave potential curve of Fe-SNC cathode oxygen reduction catalyst 6 prepared by calcining in argon atmosphere in Example 6 of the present invention is shown. Figure 7 As shown, it can be seen that compared with the argon atmosphere, the Fe-SNC cathode oxygen reduction catalyst 3 prepared under the conditions of 10% volume of hydrogen and argon mixed atmosphere has a higher half-wave potential. The reason is that 10% volume of hydrogen not only provides a reducing atmosphere, but also etches the nitrogen-coated nitrogen-carbon substrate, thereby increasing the specific surface area of ​​the nitrogen-carbon substrate.

[0093] Embodiment 7:

[0094] The preparation process of this Example 7 is substantially the same as that of Example 3, except that the pyrolysis time during the chemical vapor deposition process is adjusted to 1 h, and the Fe-SNC cathode oxygen reduction catalyst 7 is prepared.

[0095] The Fe-SNC cathode oxygen reduction catalyst 7 prepared in this Example 7 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe-SNC cathode oxygen reduction catalyst 7 was found to be 0.848V.

[0096] Embodiment 8:

[0097] The preparation process of this Example 8 is substantially the same as that of Example 3, except that the molar ratio of ferrocene, thiourea, and nitrogen-coated nitrogen-carbon substrate in the chemical vapor deposition process is adjusted to 1:1:2.4 to prepare Fe-SNC cathode oxygen reduction catalyst 8.

[0098] The Fe-SNC cathode oxygen reduction catalyst 8 prepared in Example 8 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe-SNC cathode oxygen reduction catalyst 8 was found to be 0.852V.

[0099] Embodiment 9:

[0100] The preparation process of this Example 9 is substantially the same as that of Example 3, except that the molar ratio of ferrocene, thiourea, and nitrogen-coated nitrogen-carbon substrate in the chemical vapor deposition process is adjusted to 1:1:3.2 to prepare Fe-SNC cathode oxygen reduction catalyst 9.

[0101] The Fe-SNC cathode oxygen reduction catalyst 9 prepared in Example 9 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe-SNC cathode oxygen reduction catalyst 9 was found to be 0.848V.

[0102] Embodiment 10:

[0103] The preparation process of this embodiment 10 is substantially the same as that of embodiment 9, except that during the preparation of ZIF-8, the temperature of the vacuum oven is adjusted to 50° C. to prepare the Fe-SNC cathode oxygen reduction catalyst 10.

[0104] The Fe-SNC cathode oxygen reduction catalyst 10 prepared in this embodiment 10 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe-SNC cathode oxygen reduction catalyst 10 was found to be 0.850V.

[0105] Embodiment 11:

[0106] The preparation process of this embodiment 11 is substantially the same as that of embodiment 9, except that when preparing the nitrogen-coated nitrogen-carbon substrate, the mass ratio of ZIF-8 to o-phenanthroline is adjusted to 8:1, and the Fe-SNC cathode oxygen reduction catalyst 11 is prepared.

[0107] The Fe-SNC cathode oxygen reduction catalyst 11 prepared in this Example 11 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe-SNC cathode oxygen reduction catalyst 11 was found to be 0.857V.

[0108] Embodiment 12:

[0109] The preparation process of this embodiment 12 is substantially the same as that of embodiment 9, except that the pyrolysis temperature during the chemical vapor deposition process is adjusted to 1000° C. to prepare the Fe-SNC cathode oxygen reduction catalyst 12.

[0110] The Fe-SNC cathode oxygen reduction catalyst 12 prepared in this Example 12 was subjected to a cyclic voltammetry test, and the half-wave potential of the Fe-SNC cathode oxygen reduction catalyst 12 was found to be 0.853V.

[0111] It can be seen from the preparation results of Examples 1 to 12 of the present invention that the Fe-SNC cathode oxygen reduction catalyst prepared by the above steps can have a high oxygen reduction catalytic activity while maintaining a high cycle stability, and can be applied to proton exchange membrane fuel cells.

[0112] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a sulfur-doped iron Fe-SNC cathode oxygen reduction catalyst, comprising: Pyrolyzing a mixture of ZIF-8 having a regular dodecahedral framework structure and a nitrogen-containing ligand to form a nitrogen-coated nitrogen-carbon substrate, wherein the nitrogen-carbon substrate has a regular dodecahedral framework structure; The precursor iron salt, the precursor sulfur salt and the nitrogen-coated nitrogen-carbon substrate are chemically vapor deposited to obtain a sulfur-doped iron Fe-SNC cathode oxygen reduction catalyst.

2. The preparation method according to claim 1, wherein The temperature of chemical vapor deposition is 750~900℃ and the time is 2~4h; Wherein, the atmosphere of the chemical vapor deposition is a mixture of argon and hydrogen, or argon.

3. The preparation method according to claim 1, wherein The method of pyrolyzing a ZIF-8 having a regular dodecahedral framework structure and a nitrogen-containing ligand to form a nitrogen-coated nitrogen-carbon substrate comprises: Dissolving ZIF-8 and the nitrogen-containing ligand in a solvent and mixing them to obtain a suspension; The suspension is subjected to rotary evaporation, drying, and grinding in sequence to obtain nitrogen-coated ZIF-8; Under a protective atmosphere, pyrolyzing the nitrogen-coated ZIF-8 to obtain the nitrogen-coated nitrogen-carbon substrate; Wherein, the nitrogen-containing ligand includes at least one of o-phenanthroline and dopamine.

4. The preparation method according to claim 3, wherein The pyrolysis temperature is 900-1000°C and the time is 0.5-1.5h; The solvent includes a mixed solution of water and ethanol.

5. The preparation method according to claim 3, wherein: When the nitrogen-containing ligand is o-phenanthroline, the mass ratio of ZIF-8 to the nitrogen-containing ligand is (3~5):

1.

6. The preparation method according to claim 1, wherein The precursor iron salt includes at least one of ferrocene, ferrous chloride, and ferrous chloride hydrate; the precursor sulfur salt includes at least one of thiourea and sublimated sulfur; The molar ratio of the precursor iron salt, the precursor sulfur salt, and the nitrogen-coated nitrogen-carbon substrate is 1:1:(1.6-3.2).

7. The preparation method according to claim 1, wherein ZIF-8 was prepared by the following process: Dissolving zinc nitrate and dimethylimidazole in a methanol solution and mixing them to obtain a mixed solution; The mixed solution is centrifuged and dried in sequence to obtain ZIF-8.

8. The preparation method according to claim 7, wherein: The mass ratio of zinc nitrate and dimethylimidazole is (4~8):(11~15).

9. A sulfur-doped iron Fe-SNC cathode oxygen reduction catalyst prepared by the preparation method according to claims 1 to 8, comprising: A nitrogen-coated nitrogen-carbon substrate having a regular dodecahedral framework structure, wherein sulfur is loaded on the nitrogen-coated nitrogen-carbon substrate, and the sulfur interacts with the nitrogen-coated nitrogen-carbon substrate; and The active center includes Fe-N4 loaded inside the nitrogen-coated nitrogen-carbon substrate.

10. Use of the Fe-SNC cathode oxygen reduction catalyst as claimed in claim 9 in the field of proton exchange membrane fuel cell cathode technology.

Citation Information

Patent Citations

  • Iron and nitrogen co-doped carbon-oxygen reduction catalyst, and preparation method and application thereof

    CN109103468A

  • Preparation of non-noble metal / carbon composites based on metal-organic framework, non-noble metal / carbon composites and their applications

    CN109216712A

  • Preparation method of asphalt-based oxygen reduction electrocatalyst

    CN112675897A

  • Sulfur, nitrogen and monatomic iron co-doped carbon-based catalyst prepared from methionine and preparation method of sulfur, nitrogen and monatomic iron co-doped carbon-based catalyst

    CN114188550A

  • Method for preparing efficient Fe-N-C catalyst fully doped with single or multiple halogens through step-by-step heating

    CN117476957A